Versorgungs-Report: Klima und Gesundheit - Günster, Christian; Klauber, Jürgen; Robra, Bernt-Peter; Schmuker, Caroline; Schneider, Alexandra (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft mbH & Co. KG, 2021)
The current health care report examines the effects of climate change on our health and the consequences for medical care in Germany. He brings together the different perspectives of environmental epidemiology, medicine and health policy. In a total of 16 specialist articles, experts analyze the influence of climate change on the incidence of illnesses, population groups at risk and health care infrastructures. The aim of the report is to prepare current scientific findings for healthcare practice and thus to contribute to a greater awareness of the health consequences of climate change in society. The following are presented: - Climate science basics and health effects of climate change - supply-related analyzes of significant health risks and prevention recommendations - Behavior of the population based on a current Germany-wide survey - Need for adjustment at the infrastructural-organizational level The "data and analyzes" section provides comprehensive information on the frequency of illnesses and treatments in Germany.